Meeting the Culturally-Related Academic Needs of American Indian Students: A Case Study of Elva John Middle School - (:unkn) unknown (My University, 2012)
Many issues (e.g. impact of cultural hegemony, cultural mismatch,

marginalization, stereotypes) contribute to conflicting and difficult learning environments for American Indian children and other children from marginalized cultural groups. The purpose of this study is to determine how the cultural integrity of American Indian students is supported in a public school named the Elva John Middle School. The research method is a qualitative case study designed to obtain understanding about the perspectives and subsequent impact on curricular and pedagogical decisions made by the principal and four faculty members who agreed to participate in this study. Case study procedures involved data collection from interviews, direct field observations, school documents, and existing demographic and academic performance data. The findings from this study will present strategies and practices that were planned and implemented in order to meet more effectively the unique culturally related academic needs of American Indian students.
Keywords: Indian school children--Ethnic identity; Indians of North America--Education (Middle school); Indian children--Education (Middle school); Multicultural education--United States